Associations between serum levels of adiponectin and resistin and metabolic parameters in pregnant women with gestational diabetes mellitus - Bagci, H.; Melekoglu, R.; Gursu, M. F.; Akyol, A.; Bulmus, F. G. (Imr Press, 2018)
Introduction: Gestational diabetes mellitus (GDM) is defined as a glucose intolerance firstly diagnosed during pregnancy. In this study, the authors aimed to investigate the association between serum adiponectin, and resistin levels with insulin resistance and metabolic parameters in patients with GDM. Material and Methods: A total of 80 patients: 40 healthy pregnant women (control group) and 40 pregnant women diagnosed with GDM (study group) were included in this study. Serum adiponectin, resistin, glucose, insulin, HbA1c levels, and lipid parameters were measured. Insulin resistance index HOMA-IR values were calculated. Results: Serum adiponectin levels were detected to be significantly lower (p < 0.001), whereas serum resistin levels were found to be significantly higher (p = 0.004) in GDM group compared with the control group. Levels of HDL-C, LDL-C, VLDL-C, and triglycerides were similar in both groups, but the total cholesterol level was significantly higher in the GDM group (p = 0.013). In the GDM group, adiponectin levels were negatively correlated with HbA1c levels (r = -0.368; p = 0.010) but were not correlated with any other parameter. A significant positive correlation was evident between resistin levels and both total cholesterol (r = 0.476, p = 0.001), and LDL-cholesterol (r = 0.293; p = 0.033). Conclusion: The results of this study demonstrated that serum resistin levels were significantly higher and serum adiponectin levels were significantly lower in pregnant women with GDM patients compared with normoglycemic pregnants. Also, it was detected that there was no correlation between serum adiponectin and resistin levels and insulin resistance in GDM patients.
Keywords: Adiponectin; Gestational diabetes mellitus; Insulin resistance; Resistin